Workplace smoking policies in the United States: results from a national survey of more than 100, 000 workers. Issue 3 (1997) - Gerlach, K K; Shopland, D R; Hartman, A M; Gibson, J T; Pechacek, T F
Abstract : OBJECTIVE: To determine the prevalence of smoking policies in indoor work environments as reported by a nationally representative sample of workers in the United States. DESIGN: Cross-sectional survey of households within the United States. SETTING: All 50 state and the District of Columbia, 1992-93. PARTICIPANTS: Currently employed indoor workers 15 years of age and older who responded to the National Cancer Institute's Tobacco Use Supplement to the Current Population Survey (n = 100, 561). MAIN OUTCOME MEASURES: The prevalence and restrictiveness of workplace smoking policies as reported by workers currently employed in indoor workplaces in the United States. RESULTS: Most of the indoor workers surveyed (81.6%) reported that their place of work had an official policy that addressed smoking in the workplace; 46.0% reported that their workplace policy did not permit smoking in either the public/common areas--for example, restrooms and cafeterias--or the work areas of the workplace. The reporting of these "smoke-free" policies varied significantly by gender, age, race/ethnicity, smoking status, and occupation of the worker. CONCLUSIONS: Although nearly half of all indoor workers in this survey reported that they had a smoke-free policy in their workplace, significant numbers of workers, especially those in blue-collar and service occupations, reported smoke-free rates well below the national average. If implemented, the US Occupational Safety and Health Administration's proposed regulation to require worksites to be smoke-free has the potential to increase significantly the percentage of American workers covered by these policies and to eliminate most of the disparity currently found across occupational groups.